In vivo quantitative imaging of tumor pH by nanosonophore assisted multispectral photoacoustic imaging - Janggun Jo (Nature Portfolio, 2017)
Background optical absorption of several biomolecules impedes an effective in vivo pH imaging in tumors. Here, the authors developed a visible light-based in vivo pH mapping method by coupling photoacoustic imaging and pH-responsive modified nanoparticles that selectively target tumor cells.